Văn học Việt Nam thế kỷ XX : Truyện ngắn 1945-1975. Q.2, T.9 - Phan Cự Đệ; Bùi Việt Thắng; Hà Văn Đức; Lý Hoài Thu; Hồ Thu Giang; Nguyễn Thị Hương Giang (Hà Nội : Văn học, 2004)
Kim Lân; Cao Tiến Lê; Nguyễn Thành Long; Lê Lựu; Hữu Mai; Lê Minh; Vũ Tú Nam.
Keywords: Văn học Việt; Truyện ngắn Việt, -- 1945-1975.